KAJIAN SEJARAH TARI ZAPIN ARAB DI KOTA PONTIANAK - Syarifah Meyfira Nazlia Fuaddah; Ismunandar Yahya; Winda Istiandini (Universitas Tanjungpura, 2020)
AbstractThe background of this study is the interest of researchers in the arts that are influenced by Islam and art that has long faded among the Pontianak community as well as researcher’s interest in the uniqueness of dance in Pontianak. One of the tradition is Zapin Arab dance, so researchers wanted to explain and told the detail ofthe history of Zapin Arab Dance and the development of Zapin Arab dance in Pontianak. The goal was to find out about the history of Zapin Arabic by documenting in writing form and supported by photographs of Zapin Arab performance, so that the history of Zapin Arabic dance could be known by the people of Pontianak City and the society. The method used is a historical method, with qualitative research. The research approach used is a multidisciplinary. The data sources in this study are primary and secondary sources, where primary data were obtained from five sources who studied the history of Zapin Arabic dance trips and secondary sources were obtained from books sources that relating to Zapin dance. Data collection techniques consist of book study, observation, interviews, and documentation. The technique of testing validity data uses triangulation of sources and techniques. The history of Zapin Arabic dance comes from the word